Towards engineering whole bones through endochondral ossification - Sheehy, Eamon John (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
A number of clinical situations exist where bone regeneration is required in large quantities, such as for the treatment of critical size bone defects and for the replacement of whole bones lost due to trauma or disease. The current ‘gold standard’ treatment is implantation with an autologous bone graft, harvested from the patient’s own body. Drawbacks of this approach include donor site morbidity, and a limitation on the quantity of tissue available for harvest, which have motivated the search for alternative novel strategies, aimed at bone regeneration. The field of tissue engineering aims to regenerate or replace damaged tissues through a combination of cells, three-dimensional scaffolds and signalling molecules. To date, bone tissue engineering applications have generally focussed on the direct osteogenic priming of mesenchymal stem cell (MSC) seeded scaffolds in a process resembling intramembranous ossification. Limitations associated with the traditional intramembranous approach have led to increased interest in the tissue engineering of hypertrophic cartilaginous constructs in vitro that remodel into bone in vivo, thereby recapitulating the process of endochondral ossification.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin